Is there any differences in magnetic resonance imaging findings of painful temporomandibular joint between patients with and without vertigo? - Fatih Çiçek Muhammed; Kirarslan Özge; Iğneci Mehmet; Tuncay Ezgi; Koca Cansu Gul (Balkan Stomatological Society, 2022)
Background/Aim: Temporomandibular disorder (TMD) is an umbrella term and consists of pathological situations about temporomandibular joint (TMJ) internal structure, masticatory muscle and associated structures. Otalgic complaints are included in the group of complaints within TMJ associated structures and are frequently seen with TMD. The aim of this study is to evaluate the magnetic resonance imaging findings (MRI) of patients who had unilateral pain in the preauricular region, diagnosed with vertigo. Material and Methods: The present retrospective and cross-sectional clinical study was carried out on patients presenting with preauricular pain referred to XXX University Faculty of Dentistry Department of Oral and Maxillofacial Surgery between 2018 and 2020. There were 2 groups as vertigo and health groups. MRI findings were the primary predictor variables, while pain was the primary outcome variable, recorded on a visual analog scale (VAS). Results: 120 patients were included in the study. The patients included in both groups are between 19 and 65 years of age and there is no significant statistical difference between mean ages of the groups (p>0.05). The VAS values varies between 6 and 9 in both groups. There is no significant statistical difference between mean VAS values of the groups (p>0.05). On the painful side there is no significant difference between the groups in terms of disc/condyle relation (p>0.05). On the other hand moderate effusion (61.4%) was significantly higher in the healthy group while severe effusion (54%) was significantly higher in the vertigo group (p<0.01). Conclusions: Although both groups had the same pain scale, it was observed that the vertigo group had more dramatic MRI findings in terms of disc/condyle relation and presence of effusion. This study is the first to evaluate the disc/condyle relation and the presence of effusion through MRI in vertigo patients diagnosed with TMD.